2019
DOI: 10.1002/jlb.2vma0818-328r
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induces toxicity, causes autophagy, and partially reverses dexamethasone resistance in Jurkat T cells

Abstract: Estrogens demonstrate biological activity in numerous organ systems, including the immune system, and exert their effects through estrogen receptors (ER) of two types: intracellular ERα and ERβ that activate transcriptional factors and membrane G protein‐coupled ER GPER. The latter is capable to mediate fast activation of cytosolic signaling pathways, influencing transcriptional events in response to estrogens. Tamoxifen (TAM), widely used in chemotherapy of ERα‐positive breast cancer, is considered as an ERα … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 77 publications
1
33
0
Order By: Relevance
“…Tamoxifen, an ERα antagonist, regulates both non‐neoplastic and malignant hematopoietic cells 24 and promotes the apoptosis‐inducting effect of ceramide for leukemia and other cancers 25 . Furthermore, tamoxifen is also considered a G protein‐coupled estrogen receptor (GPER) agonist and suppresses the proliferation of Jurkat cells, a T‐ALL cell line expressing GPER 26 . GPER promotes the survival of mantle cell lymphoma cells 27 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Tamoxifen, an ERα antagonist, regulates both non‐neoplastic and malignant hematopoietic cells 24 and promotes the apoptosis‐inducting effect of ceramide for leukemia and other cancers 25 . Furthermore, tamoxifen is also considered a G protein‐coupled estrogen receptor (GPER) agonist and suppresses the proliferation of Jurkat cells, a T‐ALL cell line expressing GPER 26 . GPER promotes the survival of mantle cell lymphoma cells 27 .…”
Section: Discussionmentioning
confidence: 85%
“…25 Furthermore, tamoxifen is also considered a G proteincoupled estrogen receptor (GPER) agonist and suppresses the proliferation of Jurkat cells, a T-ALL cell line expressing GPER. 26 GPER promotes the survival of mantle cell lymphoma cells. 27 Therefore, our results suggest that GC-derived lymphomas, including FL, 1,2 might be driven by apoptosis via the application of tamoxifen because FDCs prevent FL cells against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement of ERβ receptors on Hodgkin lymphoma cell lines by the DPN agonist inhibits their growth after autophagy induction ( 28 ). Another study showed that the anti-estrogen tamoxifen (TAM) had toxic effects on the human T-ALL cell line Jurkat and could partially bypass their resistance to dexamethasone used to treat T-ALL ( 29 ). Although counter-intuitive at first glance, this study could suggest that the anti-leukemic effects of estradiol and tamoxifen could be mediated through the G protein-coupled Estradiol Receptor (GPER) and not via classical ER, that are not bound by TAM and not expressed in several T-ALL cell lines ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In GC-resistant, in contrast to GC-sensitive ALL cell lines, autophagy is not induced by DEX (60, 164). Interestingly, a sensitization to GCs is achieved in GC-resistant Jurkat cells by a co-treatment with the autophagy-inducing drug tamoxifen (TAM) (166). Obatoclax reverts the GC resistance through the autophagy-dependent necroptosis, while knockdown of the autophagy-related gene 7 (ATG7) and BECN1 completely prevents the re-sensitization to DEX (163,164).…”
Section: Autophagy May Be Involved In Gc Responsementioning
confidence: 99%